Peripartum Bacteremias Due to Leptotrichia amnionii and Sneathia sanguinegens, Rare Causes of Fever during and after Delivery - De Martino, S. J. (American Society for Microbiology, 2004)
We report three cases of delivery and postpartum bacteremia due to unusual anaerobic bacteria in healthy young women. Leptotrichia amnionii bacteremia occurred during delivery in two mothers and was associated with fetal distress during labor. Conversely, Sneathia sanguinegens bacteremia occurred postpartum, 2 days after delivery, without consequence for the neonate.